Marketing Margin and Value of Farmer's Share on Rendang Product in Payakumbuh City - Sartika, Winda; Hartono, Budi; Utami, Hari Dwi; Radiati, Lilik Eka (Andalasian Livestock, 2024)
Rendang products can provide a considerable contribution to each marketing institution involved. The study aims to analyze the value of and marketing margin and farmer's share for producers of the beef-based rendang industry in Payakumbuh City. The research was conducted in 2022 in the central area of the rendang industry in West Sumatra, namely Payakumbuh City. The study involved twelve rendang industries that produce rendang using beef. Data were analyzed using the marketing margin and farmer's share (Fs) formulas to determine the value received by each marketing margin and the share received by rendang producers. The result showed that the average value of marketing margin based on the number of rendang variants produced (one variant, two variants, and three variants) showed that three rendang variants produced were able to provide the highest marketing margin value of 75.21%, compared to marketing margin of two rendang variants (72.85%), and one rendang variant (59.18%). Meanwhile, marketing margins based on the type of rendang variants produced are sliced rendang (74.41%), mashed rendang (75.26%), and pounded rendang (73.48%) with Fs value by sequentially 13.76%, 14.28%, and 13.58%.